The silent cry - Oe, Kenzaburo (Kodansha International, 1974)
Mysticism, in the sense of a “longing for God,” has been present in all times, cultures, and religions. But Soelle believes it has never been more important than in this age of materialism and fundamentalism. The antiauthoritarian mystical element in each religion leads to a community of free spirits and resistance to the death-dealing aspects of our contemporary culture. Religion in the third millennium, Soelle argues, either will be mystical or it will be dead.